Public Value Mapping in Palm Oil Trade Governance: A Case Study from Nagan Raya, Indonesia - Ilhamsyah, Fadhil; Kismartini, Kismartini; Putranti, Ika Riswanti; Lituhayu, Dyah (Universitas Teuku Umar, 2026)
This study aims to map the public values articulated by stakeholders in the governance of Fresh Fruit Bunches (FFB) trade in Nagan Raya District, Aceh, Indonesia. Using the Public Value Mapping (PVM) approach and a qualitative case study design, data were collected through in-depth interviews with 15 key actors including smallholder farmers, palm oil mills, collecting agents, farmer organizations, government officials, academics, and media supplemented by observation and document analysis. The findings reveal an asymmetry in public value accommodation, where dominant actors such as mills and agents enjoy high value alignment, while farmers, academics, and media experience marginalization. Values related to efficiency and supply continuity are more readily accommodated than those concerning justice, transparency, and participation. These results indicate the presence of public value failure, driven by market dominance, weak regulatory capacity of government institutions, and the absence of strong reflective actors. The study underscores the urgency of inclusive governance reform, strengthening farmer organizations, and enhancing the active role of academics and media in promoting a more equitable trading system. The PVM approach proves relevant in capturing value dynamics within agribusiness systems and contributes to advancing governance studies in the local palm oil sector.